Pemberian Dosis Anjuran Berbagai Pupuk Organik Pada Medium Untuk Pertumbuhan dan Produksi Tanaman Caisim ( Brassica Rava cv ) - Marlisa '; Fetmi Silvina; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
ABSTRACT Caisim is one of the many leafy vegetables marketed, in addition to foodstuffs can also be used for the treatment of various diseases, among others, to cure headaches, blindness disease, blood purifier, improves digestion and mempelancar, fever, sore throat, anti- cancer. Research objective was to repair work function studies to determine the effect of organic fertilizer for best growth and production caisim (Brassica rava cv). This research has been conducted in UPT (Technical Implementation Unit) experimental farm of Faculty of Agriculture University of Riau, Pekanbaru. This study was conducted over three months , starting from October to December 2011. Experiment was conducted using a completely randomized design (CRD) consisting of 5 treatments. Each treatment was repeated 5 times to obtain 25 experimental units . The treatment in this study was a control without fertilizer (P0), compost fertilizer TKKS 30 tonnes/ha (P1), chicken manure 20 tonnes/ha (P2), bokashi rice straw 5 tonnes/ha (P3) and fertilizer mashitam 0.5 tonnes/ha (P4). Data were obtained and analyzed statistically using analysis of varience (ANOVA). and followed by Dunnet test at the 5% level . The parameters measured were plant height (cm), root length (cm), leaf area (cm2), plant fresh weight (kg/plot) and the fresh weight of plants consumed (kg /plot). The results showed that chicken manure 20 tonnes /ha and composted oil palm empty fruit bunche (TKKS) 30 tonnes/ha gave the best results on the growth and yield of caisim. Keywords : caisim , recommended dosage , a variety of organic fertilizers